Nursing Care for Patients with Atrial Flutter Undergoing Catheter Ablation: Integrative Review - , Yasmin Martins de Sousa, Alessandra Trindade de Moura Felipe, Deisiane da Silva Mesquita Serfaty, Andréa Maria da Silva Luz, Karina Faine Freitas Takeda, Natasha Cristina Oliveira Andrade, Danielle Etienne de Oliveira Bezerra Lima, Camila Carvalho do Vale, Suziane do Socorro dos Santos, Marcela Raíssa Asevedo Dergan, Perla Katheleen Valente Corrêa, Maria de Lourdes Maia de Moraes de Carvalho; et al. (Archives of Current Research International, 2024)
Cardiac arrhythmias are electrical changes in the heart, causing an increase or decrease in the heartbeat, whether regular or irregular. Atrial Flutter is characterized by increasing atrial rate, and maintains regularity, but affects quality of life and can compromise Hemodynamic stability, treatment can be by Catheter Ablation, an invasive procedure performed in Hemodynamics. The objective of this study was to describe the Nursing Care provided to patients with Atrial Flutter undergoing Catheter Ablation. This is an Integrative Review of the Literature, in the databases: Scielo, BDENF, and Google Scholar in the last ten years, the sample consisted of 12 articles. Two categories were listed on the theme: Nursing Care in the pre-, Trans, and Post-procedure and Systematization and Systematization of Nursing Care. The nursing diagnoses were derived from the studies and included fear, risk of infection, risk of adverse response to iodinated contrast medium, acute pain and risk of decreased cardiac tissue perfusion. It was concluded that the description of the Nurse's performance in this procedure provides knowledge and promotes the populations health, since this research offers current data on care on the subject. It was evidenced that nursing care in this diagnosis is not so specific, but in general for cardiac catheter procedures in the Hemodynamics sector.